Susceptibility of Brown Planthopper (Nilaparvata lugens Stal.) from Cipunagara and Banyuwangi Population to Neem Oil Formulation - Neneng Sri Widayani; Danar Dono; Yusup Hidayat (CROPSAVER, 2018)
Brown Planthopper is one of the pests that cause problems in rice production. This study was conducted to know the tendency of using a kind of insecticide and to examined the susceptibility of brown planthopper from field population (Cipunagara, West Java) compared to standard population (Banyuwangi, East Java) to formulation insecticide of neem oil 50 EC. Observations wereconducted on Cipunagara farmers to find out the kind of insecticide used and the number of insecticide applications in one season. the susceptibility test to neem oil 50 EC formulation was conducted by root dipping method. Brown planthopper was feed on treated plant for two days and then the next day the Brown Planthopper was fed on rice plant without treatment until the eighth day. Test insects used are brown planthopper instar 4th. Observations of insect mortality test for ten days with an interval of every 24-hour observation. Susceptibility values for neem oil insecticide formulations were determined based on the resistance ratio (RR) by comparing the LC50 value of the field population and standard population. Result of the observations showed that the farmers in the Padamulya village, Cipunagara district generally using synthetic insecticides to control of this pest. The active ingredient of most mentioned was imidacloprid with a lot of different applications. The result of examination of insecticide formulation of neem oil 50 EC using the root dipping method showed that a slow death trend and the highest mortality at eight days after application. The LC50 value of neem oil 50 EC insecticide against brown planthopper in the field population (Cipunagara) was 0.36% and RR 0.98. The result indicated that brown planthopper origin from Cipunagara was still susceptible to neem oil 50 EC insecticide formulation.Keyword: Neem oil formulation, Susceptilbility, Resistance ratio, Brown Planthopper